Spinning, drawing and physical properties of polypropylene nanocomposite fibers with fumed nanosilica - I. Dabrowska; L. Fambri; A. Pegoretti; M. Slouf; T. Vackova; J. Kolarik (eXPRESS Polymer Letters, 2015)
Nanocomposite fibers of isotactic polypropylene – fumed silica AR805 were prepared by melt compounding using a two-step process: melt-spinning and hot drawing at various draw ratios up to 15. Transmission electron microscopy revealed uniform dispersion of the silica nanoparticles in polypropylene matrix, although at higher concentrations and lower draw ratios the nanoparticles showed increasing tendency to form small agglomerates. On the other hand, at low concentrations the uniform distribution of fumed silica improved mechanical properties of the composite fibers, especially at higher draw ratios. Crystallinity and melting temperature of fibers were found to significantly increase after drawing. Elastic modulus at draw ratio = 10 rose from 5.3 GPa for neat PP up to 6.2–8.1 GPa for compositions in the range 0.25–2 vol% of the filler. Moreover, higher tensile strength and creep resistance were achieved, while strain at break was rather insensitive to the filler fraction. Considering all experimental results, a failure model was proposed to explain the toughness improvement during the drawing process by the induced orientation of polymer chains and the formation of voids.